Work-family conflict, family-work conflict and job satisfaction: a study of female employees in commercial banking industry in Klang Valley / Norzafeera Amira Abu Samah ... [et al.] - Abu Samah, Norzafeera Amira; Zakaria, Ridhawati; Hussein, Norashikin; Abg Abdullah, Dayang Nailul Munna; Dahalan, Noor Azura; Mohamed, Suhaila (Universiti Teknologi Mara Selangor, 2023)
Work-family and family-work conflicts among female employees occurred primarily because of the Covid-19 pandemic and the new normal, which require these female employees to alter their daily routines immediately. This study aimed to determine the relationship between work-family conflict, family-work conflict, and job satisfaction among female employees in the commercial banking industry in Klang Valley. This study also aimed to determine the level of job satisfaction of these female employees, including intrinsic and extrinsic job satisfaction. 189 female employees from four major local commercial banks participated in this study. The data was collected via a Google Form-based online questionnaire. The data was analyzed using IBM SPSS Statistics 25. Descriptive analysis was used to determine the level of job satisfaction among female employees in the banking industry. Based on the regression analysis, it was found that work-family conflict and family-work conflict did not have a significant relationship to job satisfaction (intrinsic and extrinsic). Hopefully, this study will provide commercial banks, human resource practitioners, and employees with a better understanding of the elements that drive work-family conflict, family-work conflict, and job satisfaction. This study may also interest future researchers since it provided further information concerning work-family conflict, family-work conflict, intrinsic and extrinsic job satisfaction, and their influence on the commercial banking industry.